Spatiotemporal Evolution of Landscape Patterns and Their Driving Forces Under Optimal Granularity and the Extent at the County and the Environmental Functional Regional Scales - Nie, Wenbin; Yang, Fan; Xu, Bin; Bao, Zhiyi; Shi, Yan; Liu, Bintao; Wu, Renwu; Lin, Wei (Frontiers in Ecology and Evolution, 2022)
Research on the evolution and driving forces of landscape patterns can provide important support for ecological governance decision-making. However, the heterogeneity of landscape patterns at the microscale (grain size and extent) and the enforceability of the zoning scale at the macroscale deserve more attention. The optimal grain size (30 m×30 m) and extent (500 m) for landscape pattern research were obtained by analyzing the fluctuation of landscape metrics and semivariogram models in this study. The research area was divided into environmental functional regions (EFRs), which were defined according to the main ecological functions and protection objectives of each region. The analysis results of land use and land cover changes (LUCCs) showed that land use transfer in the past 20 years occurred mainly between woodland and cultivated land at the county scale, but this was not always the case in EFRs. The results of the landscape pattern analysis showed that landscape fragmentation, aggregation and heterogeneity increased at the county scale during 1999-2020. Moreover, except within agricultural environmental protection areas (AEP) and living environment guaranteed areas (LEG), the degree and speed of landscape damage decreased by 2020, and the turning point occurred in 2006-2013. The analysis results of geographical detectors showed that the elevation (DEM) and GDP were the main driving factors in most regions. At the county scale, the average explanatory power of the selected factors increased by 13.27% and 16.16% in 2006-2013 and 2013-2020, respectively. Furthermore, the study area was divided into three categories according to the intensity of human disturbance. Areas with high human disturbance need to increase land use intensification and strengthen the development in low-slope hill region. Areas of moderate human disturbance need to focus on improving the connectivity of ecological patches and optimizing industrial structures. Attention should be given to the monitoring of natural drivers and policy support for ecological governance in low human disturbance areas. The methods and findings in this study can provide a reference for decision-makers to formulate land use policies, especially for integration into relevant urban planning, such as the spatial planning of national land that is being widely implemented in China.